2022
DOI: 10.30616/ajb.999973
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of in vitro sterilization for pistachio (Pistacia vera L.) rootstocks

Abstract: Pistachio (Pistacia vera L.) is one of the leading edible nut consumed all over the World due to its nutritional values. The plant is cultivated in most of the countries alongwith Turkey which is one of the the leading grower of pistachio. In Turkey, the rootstock material is currently propagated through traditional methods and there is a need of propagating plant material using modern biotechnological techniques like plant tissue culture. The provision of contaminated free explants with minimum or no phenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The response of HgCl 2 varied with the duration of treatment and concentration of HgCl 2 . It was observed that 0.2 to 0.5% (w/v) HgCl 2 to sterilized MM 106 rootstocks axillary buds was best to remove contamination [22].…”
Section: Sterilizationmentioning
confidence: 99%
“…The response of HgCl 2 varied with the duration of treatment and concentration of HgCl 2 . It was observed that 0.2 to 0.5% (w/v) HgCl 2 to sterilized MM 106 rootstocks axillary buds was best to remove contamination [22].…”
Section: Sterilizationmentioning
confidence: 99%
“…Huwa San TR-50 at a concentration of 10% was used for surface decontamination of initial pistachio shoot explants. It was less effective than HgCl2 in eliminating surface contaminants and less damaging to the explants (Korkmaz et al 2022). In plant protection Linley et al (2012) indicate that agents based on silver-stabilized hydrogen peroxide are more and more commonly used as biocides, especially since their environmental toxicity is lower than that of synthetic pesticides.…”
Section: In Disinfection Of Surfaces and Storage Chambersmentioning
confidence: 99%